TELA’AH ASAS ASAS PENDIDIKAN AKHLAQ ISLAM MENURUT MIQDAD YALJIN - Wimbadi, Ardan; Robiqoh, Ilma Umi (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
Declining student morals is a problem in modern education. Miqdad Yaljin, in his book "Islamic Moral Education According to Miqdad Yaljin," emphasizes the importance of moral and religious education in forming individual character. This research uses the research library method to collect and analyze data. The results show that the principles of Islamic moral education according to Yaljin include aqidah, science, humanity and reciprocity. Correct faith is the main foundation, education must be scientific, cover all aspects of life, and the reciprocity between rewards and punishments is important. Yaljin's books played an important role in the development of Islamic morals.